Implementasi Project Based Learning dengan Pengembangan e-modul dalam Perkuliahan Matematika Preneurship untuk Meningkatkan Kemampuan Analisis Data dan Resiliensi Mahasiswa - Bunga Mardhotillah; Gusmi Kholijah (Journal on Education, 2023)
Mathematics Preneurship is one of the lectures that has great potential for application Project-based learning that is highly recommended in the MBKM, because through Mathematics Preneurship lecture, students can run a business While applying his mathematical knowledge through sharpening his business-related data analysis skills. This integrated Project Based Learning (PjBL) learning model can provide opportunities for designing his own study by creating products/services that are integrated with Data analysis skills and student resilience in doing business. This research aims to develop integrated PjBL-based e-modules Data Analysis and Student Resilience in Mathematics Preneurship Lecture. It is expected that in its application, there will be an increase in thinking skills. This research is in the form of development research by applying the development model with ADDIE procedure. The data analysis technique used is Mixed Method. Implementation of learning with projects on Mathematics Preneurship lecture as a form of learning innovation. This learning innovation will be presented in the form of projects for the achievement of graduate learning outcomes, Student resilience, knowing the results of conceptual feasibility, lecturer assessment, and student response. Implementation of learning-based The project in the Mathpreneurship lecture gives hope that business, industry and service innovation can presented by students in order to create jobs. In addition, learning is based This project result had conclution that students will have soft skills in leading, communicating, cooperation, critical thinking, responsibility and socializing with the community. Keywords: Mathematics Preneurship, math student resilience, project based learning